PENGARUH IKLIM ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN PROVINSI KALIMANTAN SELATAN (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to determine and analyze the organizational structure and organizational commitment to the performance of employees in the Education Office Education of South Kalimantan Province. This study involved 128 respondents as the study population using census method, to collect data used in the form of a questionnaire instrument with scale measurement using Likert scale with weight 1 to 5, to determine the validity level or accuracy of the research instrument tested the validity and reliability, and multiple linear regression analysis methods (t test and F test) with SPSS 20.0 for Windows program. The test results indicate the significant Organizational Change (X1) and Organizational Commitment (X2) on the Employee Performance (Y) at the Education Office of South Kalimantan Province. The results of this study provide management implications in improving employee performance should begin with efforts to improve organizational climate and organizational commitment.